Hubungan Kualitas Pelayanan Dengan Intensi Keperilakuan Pasien Rawat Inap (Pada Rumah Sakit X di Yogyakarta) - Kurniawan, Hari (Universitas Muhammadiyah Yogyakarta, 2011)
Global era suggests that the competitive challenges of competition in the business world. The development of healt-care business is increasingly competitive, the hospital is required to provide satisfactory services to their patients. This studi aimed to analyze the relasionship between the service quality and behavioral intentions in hospital inpatients X, analyze the different slope service quality relationship beetween the above behavioral intentions and that under the tolerance zone relative to waht is in the tolerance zone, and analyze the real distinctions behavioral intentions among inpatients do not experienced service problems, experienced service problems solved and unsolved. Selvice quality variabel: tangible, reality, responsiveness, asurance, and emphaty. Behavioral intention variabel: loyality, switch, pay more, external response and internal response. Reaserch location in hospital X of Yogyakarta, the study subjects were inpatients. To know the relationship between service quality, behavioral intention to use correlation and regression analysis tools.The results show there is a positive relationship between service quality and behavioral intentions in hospotal inpatients X. There is difference in slope service quality relationship beetween the above behavioral intentions and that under the tolerance zone relative to taht in the tolerance zone. There are real differences in behavioral intentions among hospitalized patients do not solved, with the highest behavioral intentions score were inpatients do not experienced service problems but not solved, with the highst behavioral intentions score were inpatients do not experience service problems, the next highes is inpatients but not experiencing problem solved and the lowest is inpatients care but not experiencing problems solved. Based on the results off all hypotheses (H1 a, H2 b, H2 a, H2 b, and H2 c) is accepted. Quality os service related behavioral intentions are positive, it is advisable to keep a hospital X servive quality issues.